2021
DOI: 10.1111/jonm.13287
|View full text |Cite
|
Sign up to set email alerts
|

Impact of engagement factors on nurses' intention to leave hospital employment

Abstract: Aim To determine the impact of workforce engagement factors on nurses' intention to leave their hospital. Background Nurse retention is important for safe patient care. It is unknown whether meaning and joy in work, occupational fatigue, job satisfaction and unprofessional behaviour experiences predict hospital nurse turnover intentions. Method This cross‐sectional study involved responses from 747 nurses from two south‐western hospitals. Measures included surveys to capture meaning and joy in work, job satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 40 publications
(57 reference statements)
0
27
1
Order By: Relevance
“…Two protective factors, meaning and joy in work and resilience at work, were strongly associated but did not explain variability in burnout or intention to leave in our study. In a previous study, 1 meaning and joy in work mediated the impact of chronic fatigue on turnover intention, whereas in this study, chronic fatigue is the dominant factor determining both nurse burnout and turnover intention. Among UK nurses, 29 on-the-job embeddedness, which has elements of meaning and joy in work, mediated the impact of job stress on turnover intention.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Two protective factors, meaning and joy in work and resilience at work, were strongly associated but did not explain variability in burnout or intention to leave in our study. In a previous study, 1 meaning and joy in work mediated the impact of chronic fatigue on turnover intention, whereas in this study, chronic fatigue is the dominant factor determining both nurse burnout and turnover intention. Among UK nurses, 29 on-the-job embeddedness, which has elements of meaning and joy in work, mediated the impact of job stress on turnover intention.…”
Section: Discussioncontrasting
confidence: 72%
“…This multivariate study builds on prepandemic findings among hospital nurses. 1 Nine percent of nurses in this sample reported that they intended to leave the hospital within 6 to 12 months, a number that should be alarming to nurse administrators. This is comparable with published reports among US nurses (8%) 8 but is lower than reports with international nurses: Thai clinical nurses, 10% 19 ; Australian clinical nurses, 33% 20 ; and Chinese clinical nurses, 25%.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…On the basis of the literature, fatigue and stress seem reciprocally associated; the development of one can predict the insurgence of the other, with recovery acting positively in reducing both (e.g., Winwood et al, 2005Winwood et al, , 2006Doerr et al, 2015;Blustein et al, 2016). According to this principle, Winwood et al (2005Winwood et al ( , 2006 provided an extensively used (e.g., Somantri et al, 2020;Rutledge et al, 2021) and comprehensive classification of occupational fatigue, distinguishing between acute fatigue, chronic fatigue, and persistent fatigue (Winwood et al, 2005(Winwood et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%